Controlling chaos in two coupled lasers via optoelectronic delayed time cross-feedback. Issue 1 (July 2021) - Yan, Senlin
Abstract: This paper presents an optoelectronic delayed time cross-feedback method to control chaos in two coupled lasers. The technical solution of chaos-control of two lasers is designed out to convert light from one laser into a photocurrent by a photoelectric converter, and then the delayed time photocurrent is cross added on another laser to suppress chaos or guide other dynamics behaviours. We adjust feedback levels or delayed time to realize chaos-control, and which can lead to show all kinds of dynamics states. We find that chaos of two lasers is suppressed into different cycle-one states while the cycle-one controlled region is found. We analyse also the laser's damping oscillation process for chaos-control of two lasers from chaos becoming of a cycle-one state when feedback levels shift. We find that chaos in the two lasers can be controlled in different quasi-periodic states, such as a cycle-one, cycle-2, a cycle-3, a cycle-5, and other quasi-cycle states while we find some quasi-cycle controlled distribution regions. The listed results imply that chaos-control of two coupled lasers can be effectively realized via the optoelectronic delayed time cross-feedback method. Our Result is very helpful for our studies of controlling complex dynamic systems, chaos, and laser technology.